Perbandingan Model Pemilihan Moda Feeder BMA Trans dan Mobil Sewa Kota Parepare ke Bandara Sultan Hasanuddin - Umar Ramadhan; Hamka Wakkang; Misbahuddin Misbahuddin (Jurnal Konstruksi, 2024)
Transportation concerns the movement of people and goods. Currently, the functions and types of transportation are developing according to existing needs and conditions. The aim of this research is to identify factors that influence feeder transportation on mode choice between BMA trans and rental cars in the city of Parepare to Sultan Hasanuddin airport. The results of the regression analysis are used to express probability using the binary logit regression modeling method. The mode selection model (feeder) was processed using STATA 16 software. Based on the factors that influence transportation users in choosing the mode to get to Sultan Hasanuddin Airport, the main factor for respondents who chose BMA Trans was based on the comfort factor of 48%. Meanwhile, the main factor for respondents in choosing a rental car mode in the city of Parepare to get to the airport is based on the travel time factor of 40%. and from the results of the modeling comparison between BMA Trans and rental cars, the probability increase for BMA Trans is greater in terms of cost, safety and comfort. while a rental car increases the probability in terms of travel time.